Photovoltaic ZTA ceramic material and preparation method thereof
By using monoclinic zirconia, yttrium zirconia and plate-shaped corundum in photovoltaic ceramic materials, combined with spray granulation and sintering processes, the problem of high thermal expansion stress and cost of ceramic materials at high temperatures is solved, and high strength is achieved. Ceramic materials with high toughness and thermal shock resistance meet the high performance needs of the photovoltaic field.
Patent Information
- Application Number
- CN202411491616.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-07
AI Technical Summary
Existing photovoltaic ceramic materials have stress problems caused by thermal expansion at high temperatures, and are costly, making it difficult to meet the needs of high strength, high toughness and thermal shock resistance at high temperatures.
Using zirconia toughened alumina (ZTA) ceramic material, by adding monoclinic zirconia, yttrium zirconia and plate-shaped corundum to the powder raw materials, the crystal transformation of monoclinic zirconia and the vacancy of plate-shaped corundum Structure, improve the thermal shock resistance of ceramic materials, and optimize the spray granulation and sintering process to reduce costs.
It realizes photovoltaic ceramic materials that maintain high strength and superior thermal shock resistance at high temperatures, reduces the preparation cost and meets the high performance demand for ceramic materials in the photovoltaic field.
Smart Images

Figure CN119263785A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photovoltaic materials and relates to an alumina ceramic material, in particular to a ZTA ceramic material for photovoltaics and a preparation method thereof. Background Art
[0002] The preparation process of photovoltaic silicon wafers requires high temperatures and rapid temperature rise and fall, which places high demands on high-temperature resistant inorganic materials.
[0003] Ceramics in the prior art include alumina ceramics, mullite ceramics and carbide ceramics. However, the grains of alumina ceramics are tightly bonded during the preparation process. Although they have good mechanical properties at room temperature, they expand or contract rapidly when the temperature is rapidly increased or decreased, resulting in the grain boundaries between the grains being unable to meet the spatial expansion requirements, causing stress in the alumina ceramics and a risk of fracture during use. Mullite ceramics use large-sized grains to increase the space between the grains to cope with the thermal expansion problem caused by temperature increase or decrease, but the degree of grain bonding is poor, and the mechanical properties at both room and high temperatures cannot meet the requirements of high-load work. Silicon carbide ceramics have excellent performance at high temperatures, but their cost is high, more than ten times that of general high-temperature materials, and they cannot be used in large quantities.
[0004] CN117776751A discloses a method for preparing a highly wear-resistant ZTA ceramic material, which uses zirconium oxide and aluminum oxide as the main crystal phases and nano-carbon fibers as toughening agents, but it does not involve improvements in thermal shock resistance; CN117602956A discloses an aluminum oxide photovoltaic insulating ceramic, whose raw materials include aluminum oxide, single-walled carbon nanotubes, silicon nitride and silicon dioxide, but it also does not involve improvements in thermal shock resistance. CN118026658A discloses a low-heat storage mullite sagger of high-purity aluminum oxide powder and its preparation method, but the mechanical properties and thermal shock resistance of the mullite material are poor.
[0005] Therefore, how to provide a ZTA ceramic material for photovoltaic use that has low cost, high strength, high toughness and excellent thermal shock resistance at high temperatures and a preparation method thereof is a technical problem that urgently needs to be solved in this field. Summary of the invention
[0006] The purpose of the present invention is to provide a ZTA ceramic material for photovoltaics and a preparation method thereof. The ZTA (zirconia toughened alumina) ceramic material for photovoltaics has a low preparation cost, and has high strength, high toughness and excellent thermal shock resistance at high temperatures, and can meet the increasing demand for ceramic materials in the photovoltaic field.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a ZTA ceramic material for photovoltaics. In terms of mass percentage, the powder raw materials of the ZTA ceramic material for photovoltaics include 5wt% to 18wt% of monoclinic zirconium oxide, 5wt% to 40wt% of yttrium-stabilized tetragonal zirconia, 5wt% to 21wt% of plate-like corundum and 21wt% to 79wt% of alumina.
[0009] Monoclinic zirconia maintains monoclinic crystals at room temperature, and its grain structure is tightly bound, which ensures the use conditions of ZTA ceramic materials for photovoltaics. It can also undergo a crystal transformation under high temperature conditions, from monoclinic crystals to tetragonal crystals. The crystal transformation increases the effective space at the grain boundary, alleviating the stress problem caused by high-temperature thermal expansion, thereby maintaining high strength at high temperatures. The use of plate-shaped corundum can produce partial vacancies, further improving the thermal shock resistance of ZTA ceramic materials for photovoltaics.
[0010] Preferably, the maximum length of the plate-shaped corundum is long, the thickness of the plate-shaped corundum is high, and the aspect ratio of the plate-shaped corundum is 8:1 to 12:1.
[0011] Preferably, in the raw materials for preparing the photovoltaic ZTA ceramic material, the amount of monoclinic zirconium oxide is lower than the amount of yttrium-stabilized tetragonal zirconia.
[0012] In a second aspect, the present invention provides a method for preparing the photovoltaic ZTA ceramic material as described in the first aspect, the preparation method comprising the following steps:
[0013] The powder raw material, binder, dispersant and solvent are uniformly mixed, the obtained slurry is sprayed and granulated, and then formed and sintered to obtain the photovoltaic ZTA ceramic material.
[0014] Preferably, the water content of the granulated powder obtained by the spray granulation is 0.4 wt % to 0.6 wt %.
[0015] Preferably, the granulated powder obtained by the spray granulation can pass through a sieve with a first mesh size, but cannot pass through a sieve with a second mesh size.
[0016] The first mesh number is 50 meshes to 80 meshes, and the second mesh number is 270 meshes to 325 meshes.
[0017] Preferably, the aging time is more than 18 hours.
[0018] Preferably, the one-way pressure of the molding is 150 MPa to 300 MPa.
[0019] Preferably, the heating rate of the sintering does not exceed 4°C / min.
[0020] Preferably, the sintering temperature is 1560°C to 1650°C.
[0021] Preferably, the sintering time is 2 h to 4 h.
[0022] Preferably, the mixing method comprises ball milling.
[0023] Preferably, the average particle size of the monoclinic zirconium oxide in the powder raw material is 0.8 μm to 1.2 μm.
[0024] Preferably, the average particle size of yttrium-stabilized tetragonal zirconia in the powder raw material is 0.8 μm to 1.2 μm.
[0025] Preferably, the average particle size of the plate-like corundum in the powder raw material is 0.8 μm to 1.2 μm.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] Monoclinic zirconia maintains monoclinic crystals at room temperature, and its grain structure is tightly bound, which ensures the use conditions of ZTA ceramic materials for photovoltaics. It can also undergo a crystal transformation under high temperature conditions, from monoclinic crystals to tetragonal crystals. The crystal transformation increases the effective space at the grain boundary, alleviating the stress problem caused by high-temperature thermal expansion, thereby maintaining high strength at high temperatures. The use of plate-shaped corundum can produce partial vacancies, further improving the thermal shock resistance of ZTA ceramic materials for photovoltaics. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a SEM image of the plate-shaped corundum used in Example 1.
[0029] Figure 2 This is a SEM image of the ZTA ceramic material for photovoltaic use obtained in Example 1. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0031] A certain embodiment of the present invention provides a ZTA ceramic material for photovoltaics. In terms of mass percentage, the powder raw materials of the ZTA ceramic material for photovoltaics include 5wt% to 18wt% of monoclinic zirconium oxide, 5wt% to 40wt% of yttrium-stabilized tetragonal zirconia, 5wt% to 21wt% of plate-like corundum, 3wt% to 5wt% of inorganic oxides and 21wt% to 79wt% of aluminum oxide.
[0032] Zirconia maintains monoclinic crystals at room temperature. The crystal structure is tightly combined, which can ensure the use conditions under room temperature conditions. It can also undergo a crystal transformation under high temperature conditions, from monoclinic crystals to tetragonal crystals. After the crystal transformation, the effective space at the grain boundary increases, which alleviates the stress problem caused by high-temperature thermal expansion and can maintain high strength at high temperatures. Due to the structural irregularity of tabular corundum, partial vacancies can be generated, further improving the material's thermal shock resistance.
[0033] Specifically, the present invention utilizes the property that monoclinic zirconia has a reversible crystal transformation at high temperature. During the preparation process of ZTA ceramic materials for photovoltaics, the crystal transformation leads to the generation of space inside the ZTA ceramic materials for photovoltaics. This part of the space can be used for thermal expansion of grains, thereby enhancing the thermal shock resistance of the ZTA ceramic materials for photovoltaics. Under high temperature conditions, the monoclinic zirconia is transformed into a tetragonal phase with better stability, thereby enhancing the high-temperature performance of the ZTA ceramic materials for photovoltaics and compensating for the defect that the performance of the ceramic materials decreases at high temperatures. Tabular corundum can leave a large amount of space vacancies during the preparation process of ZTA ceramic materials for photovoltaics, thereby further improving the thermal shock resistance of the ceramic materials and compensating for the defect that the price of zirconia is too high.
[0034] In the powder raw material of ZTA described in the present invention, the mass percentage of monoclinic zirconium oxide is 5wt% to 18wt%, for example, it can be 5wt%, 8wt%, 10wt%, 12wt%, 15wt% or 18wt%, but is not limited to the listed values, and the remaining values not listed in the numerical range are also applicable.
[0035] The yttrium-stabilized tetragonal zirconia described in the present invention is composed of zirconium oxide and yttrium oxide, and the total molar percentage of zirconium oxide and yttrium oxide is 100%, wherein the molar percentage of yttrium oxide is 3% to 8%, for example, it can be 3%, 4%, 5%, 6% or 8%, but is not limited to the listed values, and the remaining unlisted values within the numerical range are also applicable.
[0036] In the powder raw material of ZTA described in the present invention, yttrium-stabilized tetragonal zirconia accounts for 5wt% to 40wt% of the powder raw material, for example, it can be 5wt%, 6wt%, 11wt%, 16wt%, 21wt%, 27wt%, 31wt%, 36wt% or 40wt%, but is not limited to the listed values, and the remaining values not listed in the numerical range are also applicable.
[0037] The plate-like corundum in the present invention can further improve the thermal shock resistance of the ZTA ceramic material for photovoltaics. When the amount of the plate-like corundum is too small, the thermal shock resistance of the ZTA ceramic material for photovoltaics is not significantly improved; and when the amount of the plate-like corundum is too large, it will have an adverse effect on the mechanical properties of the ZTA ceramic material for photovoltaics. Therefore, in the powder raw material of the ZTA ceramic material for photovoltaics described in the present invention, the mass percentage of the plate-like corundum is 5wt% to 21wt%, for example, it can be 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 18wt%, 20wt% or 21wt%, but is not limited to the listed values, and the remaining values not listed within the numerical range are also applicable.
[0038] In the present invention, the total mass percentage of monoclinic zirconia, yttrium-stabilized tetragonal zirconia, plate-like corundum and alumina is 100wt%.
[0039] The appropriate aspect ratio of the plate-like corundum can ensure the thermal shock resistance of the obtained ZTA ceramic material for photovoltaics. As a preferred technical solution of the present invention, in certain embodiments, the aspect ratio of the plate-like corundum is 8:1 to 12:1, for example, it can be 8:1, 9:1, 10:1, 11:1 or 12:1, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0040] In the present invention, the length of the plate-like corundum is its maximum length, and the height of the plate-like corundum is its thickness.
[0041] In certain embodiments, in the raw materials for preparing the photovoltaic ZTA ceramic material, the amount of monoclinic zirconium oxide is lower than the amount of yttrium-stabilized tetragonal zirconia.
[0042] In the present invention, the use of monoclinic zirconia can ensure the flexural strength and thermal shock resistance of ZTA ceramic materials for photovoltaics, but pure monoclinic zirconia is unstable. When all zirconium oxide is monoclinic zirconia, it is not conducive to further improving the performance of the ceramic material. In order to balance the mechanical properties and thermal shock resistance of the obtained ceramic material, it is preferred to make the amount of monoclinic zirconia lower than the amount of yttrium-stabilized tetragonal zirconia.
[0043] A certain embodiment of the present invention provides a method for preparing the ZTA ceramic material for photovoltaic use described in any embodiment, and the preparation method comprises the following steps:
[0044] The powder raw material, binder, dispersant and solvent are uniformly mixed, the obtained slurry is sprayed and granulated, and then formed and sintered to obtain the photovoltaic ZTA ceramic material.
[0045] In some embodiments, the mixing method includes ball milling mixing. The present invention does not further limit the specific conditions of ball milling mixing, as long as the powder raw material, binder, dispersant and solvent can be uniformly mixed.
[0046] In certain embodiments, the solvent comprises water.
[0047] In the preparation method provided by the present invention, the use of dispersants and binders is to achieve uniform dispersion of materials in the slurry. The present invention does not specifically limit their dosage and types, as long as the purpose of uniform dispersion can be achieved.
[0048] Spray granulation can ensure the uniform dispersion of various materials in the granulation powder, and controlling the water content of the granulation powder can enhance the plasticity of the granulation powder, which is convenient for subsequent molding.
[0049] In certain embodiments, the water content of the granulated powder obtained by spray granulation is 0.4wt% to 0.6wt%, for example, 0.4wt%, 0.5wt% or 0.6wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0050] In certain embodiments, the granulated powder obtained by the spray granulation can pass through a first mesh sieve but cannot pass through a second mesh sieve.
[0051] The first mesh number is 50 meshes to 80 meshes, and the second mesh number is 270 meshes to 325 meshes.
[0052] If the particle size of the granulation powder is too large, it will easily lead to a large number of pores in the ZTA ceramic material for photovoltaics; if the particle size of the granulation powder is too small, it will cause the ZTA ceramic material for photovoltaics to crack and deform. In order to make the obtained ZTA ceramic material for photovoltaics have good mechanical properties, the granulation powder needs to be able to pass through the first mesh sieve and not pass through the second mesh sieve.
[0053] Among them, the first mesh number is 50 mesh to 80 mesh, for example, it can be 50 mesh, 55 mesh, 60 mesh, 65 mesh, 70 mesh, 75 mesh or 80 mesh, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] The second mesh number is 270 mesh to 325 mesh, for example, it can be 270 mesh, 280 mesh, 300 mesh, 310 mesh or 325 mesh, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] In order to evenly distribute the moisture in the granulated powder, in certain embodiments, the preparation method further comprises aging after spray granulation and before molding.
[0056] In some embodiments, the aging time is more than 18 hours, for example, it can be 18 hours, 20 hours, 21 hours, 24 hours or 25 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In some embodiments, the unidirectional pressure of molding is 150 MPa to 300 MPa, for example, 150 MPa, 180 MPa, 200 MPa, 250 MPa, 280 MPa or 300 MPa. Within this pressure range, stable molding can be achieved and the molding effect can be improved.
[0058] In the present invention, the heating rate during sintering affects the cracking problem of the obtained ceramic material. Therefore, selecting a suitable heating rate can avoid cracking generated during the preparation process.
[0059] In some embodiments, the sintering heating rate does not exceed 4°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min or 4°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] In some embodiments, the sintering temperature is 1560°C to 1650°C, for example, 1560°C, 1580°C, 1600°C, 1620°C or 1650°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] In some embodiments, the sintering time is 2 hours to 4 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0062] In some embodiments, the average particle size of monoclinic zirconium oxide in the powder raw material is 0.8 μm to 1.2 μm, for example, it can be 0.8 μm, 0.9 μm, 1 μm, 1.1 μm or 1.2 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0063] In some embodiments, the average particle size of yttrium-stabilized tetragonal zirconia in the powder raw material is 0.8 μm to 1.2 μm, for example, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm or 1.2 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0064] In some embodiments, the average particle size of the plate-like corundum is 0.8 μm to 1.2 μm, for example, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm or 1.2 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0065] Example 1
[0066] The present embodiment provides a photovoltaic ZTA ceramic material. In terms of mass percentage, the powder raw material of the photovoltaic ZTA ceramic material includes 79wt% of α-Al2O3, 5wt% of monoclinic zirconium oxide, 11wt% of yttrium-stabilized tetragonal zirconia (5% of yttrium oxide by mole), and 5wt% of plate-like corundum (SEM image as shown in FIG. Figure 1 shown);
[0067] Among them, the aspect ratio of tabular corundum is 10:1, and the average particle size is 1μm;
[0068] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0069] The preparation method of the photovoltaic ZTA ceramic material in this embodiment includes the following steps:
[0070] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0071] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0072] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0073] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0074] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0075] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0076] (4) The formed blank was heated to 1600° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the photovoltaic ZTA ceramic material (SEM image as shown in FIG. Figure 2 shown).
[0077] Example 2
[0078] This embodiment provides a photovoltaic ZTA ceramic material. In terms of mass percentage, the powder raw material of the photovoltaic ZTA ceramic material includes 79wt% of α-Al2O3, 8wt% of monoclinic zirconium oxide, 8wt% of yttrium-stabilized tetragonal zirconia (5% of yttrium oxide by mole), and 5wt% of plate-like corundum.
[0079] Among them, the aspect ratio of tabular corundum is 10:1, and the average particle size is 1μm;
[0080] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0081] The preparation method of the photovoltaic ZTA ceramic material in this embodiment includes the following steps:
[0082] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0083] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0084] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0085] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0086] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0087] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0088] (4) The formed blank is heated to 1520° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the photovoltaic ZTA ceramic material.
[0089] Example 3
[0090] This embodiment provides a photovoltaic ZTA ceramic material. In terms of mass percentage, the powder raw material of the photovoltaic ZTA ceramic material includes 79wt% of α-Al2O3, 11wt% of monoclinic zirconium oxide, 5wt% of yttrium-stabilized tetragonal zirconia (5% by mole of yttrium oxide) and 5wt% of plate-like corundum.
[0091] Among them, the aspect ratio of tabular corundum is 10:1, and the average particle size is 1μm;
[0092] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0093] The preparation method of the photovoltaic ZTA ceramic material in this embodiment includes the following steps:
[0094] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0095] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0096] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0097] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0098] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0099] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0100] (4) The formed blank is heated to 1520° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the photovoltaic ZTA ceramic material.
[0101] Example 4
[0102] This embodiment provides a photovoltaic ZTA ceramic material. In terms of mass percentage, the powder raw material of the photovoltaic ZTA ceramic material includes 79wt% of α-Al2O3, 5wt% of monoclinic zirconium oxide, 11wt% of yttrium-stabilized tetragonal zirconia (5% of yttrium oxide by mole), and 5wt% of plate-like corundum.
[0103] Among them, the aspect ratio of tabular corundum is 10:1, and the average particle size is 1μm;
[0104] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0105] The preparation method of the photovoltaic ZTA ceramic material in this embodiment includes the following steps:
[0106] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0107] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0108] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0109] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0110] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 50-mesh sieve but cannot pass through a 270-mesh sieve; the granulated powder has a moisture content of 0.4 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0111] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, quinoline, YZSM) at a mass percentage of 0.3% of the granulated powder, and then a uniaxial pressure of 250 MPa is applied for molding;
[0112] (4) The formed blank is heated to 1650° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 4 h to obtain the photovoltaic ZTA ceramic material.
[0113] Example 5
[0114] This embodiment provides a photovoltaic ZTA ceramic material. In terms of mass percentage, the powder raw material of the photovoltaic ZTA ceramic material includes 79wt% of α-Al2O3, 5wt% of monoclinic zirconium oxide, 11wt% of yttrium-stabilized tetragonal zirconia (5% of yttrium oxide by mole), and 5wt% of plate-like corundum.
[0115] Among them, the aspect ratio of tabular corundum is 10:1, and the average particle size is 1μm;
[0116] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0117] The preparation method of the photovoltaic ZTA ceramic material in this embodiment includes the following steps:
[0118] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0119] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0120] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0121] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0122] (2) spray granulation of the slurry to obtain granulated powder that can pass through an 80-mesh sieve but cannot pass through a 325-mesh sieve; the moisture content of the granulated powder is 0.6 wt %, and then the granulated powder is aged for 18 hours to make the moisture in the granulated powder evenly distributed;
[0123] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 300 MPa is applied for molding;
[0124] (4) The formed blank is heated to 1560° C. at a rate of 4° C. / min in a high temperature furnace and pressureless sintered for 3 h to obtain the ZTA ceramic material for photovoltaic use.
[0125] Example 6
[0126] This embodiment provides a ZTA ceramic material for photovoltaic use, which is the same as that of Embodiment 1 except that the sintering temperature is 1560°C.
[0127] Example 7
[0128] This embodiment provides a ZTA ceramic material for photovoltaic use, which is the same as that of Embodiment 1 except that the sintering temperature is 1650° C.
[0129] Example 8
[0130] This embodiment provides a photovoltaic ZTA ceramic material. In terms of mass percentage, the powder raw material of the photovoltaic ZTA ceramic material includes 39wt% of α-Al2O3, 5wt% of monoclinic zirconium oxide, 35wt% of yttrium-stabilized tetragonal zirconia (5% of yttrium oxide by mole), and 16wt% of plate-like corundum.
[0131] Among them, the aspect ratio of tabular corundum is 8:1, and the average particle size is 1μm;
[0132] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0133] The preparation method of the photovoltaic ZTA ceramic material in this embodiment includes the following steps:
[0134] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0135] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0136] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0137] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0138] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0139] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0140] (4) The formed blank is heated to 1600° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the photovoltaic ZTA ceramic material.
[0141] Example 9
[0142] This embodiment provides a photovoltaic ZTA ceramic material. In terms of mass percentage, the powder raw material of the photovoltaic ZTA ceramic material includes 21wt% of α-Al2O3, 18wt% of monoclinic zirconium oxide, 40wt% of yttrium-stabilized tetragonal zirconia (5% by mole of yttrium oxide) and 21wt% of plate-like corundum.
[0143] Among them, the aspect ratio of tabular corundum is 12:1, and the average particle size is 1μm;
[0144] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0145] The preparation method of the photovoltaic ZTA ceramic material in this embodiment includes the following steps:
[0146] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0147] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0148] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0149] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0150] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0151] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0152] (4) The formed blank is heated to 1600° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the photovoltaic ZTA ceramic material.
[0153] Comparative Example 1
[0154] This comparative example provides a photovoltaic ZTA ceramic material, wherein the powder raw material of the photovoltaic ZTA ceramic material comprises, by mass percentage, 79wt% of α-Al2O3, 16wt% of monoclinic zirconium oxide and 5wt% of plate-like corundum;
[0155] Among them, the aspect ratio of tabular corundum is 10:1, and the average particle size is 1μm;
[0156] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0157] The preparation method of the ZTA ceramic material for photovoltaic use in this comparative example comprises the following steps:
[0158] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0159] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0160] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0161] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0162] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0163] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0164] (4) The formed blank is heated to 1520° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the photovoltaic ZTA ceramic material.
[0165] Comparative Example 2
[0166] This comparative example provides a photovoltaic ZTA ceramic material, in which the powder raw materials of the photovoltaic ZTA ceramic material include 79wt% of α-Al2O3, 16wt% of yttrium-stabilized tetragonal zirconia (5% of yttrium oxide by mole), and 5wt% of plate-like corundum, in terms of mass percentage;
[0167] Among them, the aspect ratio of tabular corundum is 10:1, and the average particle size is 1μm;
[0168] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0169] The preparation method of the ZTA ceramic material for photovoltaic use in this comparative example comprises the following steps:
[0170] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0171] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0172] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0173] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0174] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0175] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0176] (4) The formed blank is heated to 1520° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the photovoltaic ZTA ceramic material.
[0177] Comparative Example 3
[0178] This comparative example provides a ceramic material, wherein the powder raw material of the ceramic material comprises 95wt% of α-Al2O3 and 5wt% of SiO2 in terms of mass percentage;
[0179] The preparation method of the ceramic material in this comparative example comprises the following steps:
[0180] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0181] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0182] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0183] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0184] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0185] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0186] (4) The formed blank is heated to 1600° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the ceramic material.
[0187] Comparative Example 4
[0188] This comparative example provides a ceramic material, wherein the powder raw material of the ceramic material comprises 65wt% of α-Al2O3 and 35wt% of SiO2 in terms of mass percentage;
[0189] The preparation method of the ceramic material in this comparative example comprises the following steps:
[0190] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0191] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0192] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0193] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0194] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0195] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0196] (4) The formed blank is heated to 1600° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the ceramic material.
[0197] Comparative Example 5
[0198] This comparative example provides a ceramic material, wherein the powder raw material of the ceramic material comprises, by weight percentage, 96 wt % of SiC, 1.4 wt % of AlN, 1.6 wt % of Al2O3 and 1 wt % of Y2O3;
[0199] The preparation method of the ceramic material in this comparative example comprises the following steps:
[0200] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0201] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0202] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0203] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0204] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0205] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0206] (4) The formed blank is heated to 2200° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the ceramic material.
[0207] Comparative Example 6
[0208] This comparative example provides a ceramic material, wherein the powder raw material of the ceramic material comprises 79wt% Al2O3 and 21wt% Y2O3 in terms of mass percentage;
[0209] The preparation method of the ceramic material in this comparative example comprises the following steps:
[0210] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0211] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0212] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0213] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0214] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0215] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0216] (4) The formed blank is heated to 1600° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the ceramic material.
[0217] Performance Characterization
[0218] The density, 25° C. flexural strength, high temperature flexural strength and thermal shock resistance of the ZTA ceramic material obtained in the above embodiment and the ceramic material obtained in the comparative example were measured, and the results are shown in Table 1.
[0219] Among them, the density test method is GB / T 25995-2010 fine ceramic density and apparent porosity test method; the method described in GB / T 3001-2017 is used to test the room temperature flexural strength of refractory materials, the method described in GB / T3002-2017 is used to test the high temperature (1100℃) flexural strength of refractory materials, and the method described in GB / T 30873-2014 is used to test the thermal shock resistance of refractory materials.
[0220] Table 1
[0221]
[0222]
[0223] In summary, the present invention utilizes the reversible crystal transformation property of monoclinic zirconia at high temperature. During the preparation process of ZTA ceramic materials for photovoltaics, the crystal transformation leads to the generation of space inside the ZTA ceramic materials for photovoltaics. This part of the space can be used for thermal expansion of grains, thereby enhancing the thermal shock resistance of the ZTA ceramic materials for photovoltaics. Under high temperature conditions, the monoclinic zirconia is transformed into a tetragonal phase with better stability, thereby enhancing the high temperature performance of the ZTA ceramic materials for photovoltaics and compensating for the defect that the performance of the ceramic materials decreases at high temperatures. Tabular corundum can leave a large amount of space vacancies in the preparation process of ZTA ceramic materials for photovoltaics, thereby further improving the thermal shock resistance of the ceramic materials and compensating for the defect that the price of zirconia is too high.
[0224] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A ZTA ceramic material for photovoltaic use, characterized in that: In terms of mass percentage, the powder raw materials of the photovoltaic ZTA ceramic material include 5wt% to 18wt% of monoclinic zirconia, 5wt% to 40wt% of yttrium-stabilized tetragonal zirconia, 5wt% to 21wt% of plate-like corundum and 21wt% to 79wt% of alumina.
2. The ZTA ceramic material for photovoltaic use according to claim 1, characterized in that: Taking the maximum length of the plate-shaped corundum as the length and the thickness of the plate-shaped corundum as the height, the aspect ratio of the plate-shaped corundum is 8:1 to 12:
1.
3. The ZTA ceramic material for photovoltaic use according to claim 1 or 2, characterized in that: In the raw materials for preparing the photovoltaic ZTA ceramic material, the amount of monoclinic zirconium oxide is lower than the amount of yttrium-stabilized tetragonal zirconium oxide.
4. A method for preparing a photovoltaic ZTA ceramic material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: The powder raw material, binder, dispersant and solvent are uniformly mixed, the obtained slurry is sprayed and granulated, and then formed and sintered to obtain the photovoltaic ZTA ceramic material.
5. The preparation method according to claim 4, characterized in that: The water content of the granulated powder obtained by the spray granulation is 0.4wt% to 0.6wt%; Preferably, the granulated powder obtained by the spray granulation can pass through a first mesh sieve and cannot pass through a second mesh sieve; The first mesh number is 50 meshes to 80 meshes, and the second mesh number is 270 meshes to 325 meshes.
6. The preparation method according to claim 4 or 5, characterized in that: The preparation method also includes aging after spray granulation and before molding; Preferably, the aging time is more than 18 hours.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The one-way pressure of the molding is 150 MPa to 300 MPa.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The heating rate of the sintering does not exceed 4°C / min; Preferably, the sintering temperature is 1560°C to 1650°C; Preferably, the sintering time is 2 h to 4 h.
9. The preparation method according to any one of claims 4 to 8, characterized in that: The mixing method includes ball milling.
10. The preparation method according to any one of claims 4 to 8, characterized in that: The average particle size of the monoclinic zirconium oxide in the powder raw material is 0.8 μm to 1.2 μm; Preferably, the average particle size of the yttrium-stabilized tetragonal zirconia in the powder raw material is 0.8 μm to 1.2 μm; Preferably, the average particle size of the plate-like corundum in the powder raw material is 0.8 μm to 1.2 μm.
Citation Information
Patent Citations
98 aluminum oxide photovoltaic insulating ceramic
CN117602956A
Preparation method of high-wear-resistance ZTA ceramic material
CN117776751A
Low-heat-storage mullite sagger for sintering high-purity alumina powder and preparation method of low-heat-storage mullite sagger
CN118026658A
Preparation method of zirconium oxide toughening aluminum oxide hollow balls
CN101798230A
Alumina ceramic ring having high thermal shock resistance and used for polycrystalline silicon reduction furnace as well as preparation method
CN104788083A